STRATEGIC POLICY OF THE PRINCIPAL IN SOLVING STUDENT DISCIPLINARY PROBLEMS AT STATE VOCATIONAL SCHOOL 1 SIGLI - Sitti Mustika Rizki; Sri Rahmi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
Student indiscipline remains a major challenge in school management, especially in vocational schools. This condition requires the strategic role of the principal as a policy maker in formulating and implementing effective disciplinary policies. This study aims to examine the strategic policies of principals in dealing with student discipline issues and to identify the factors that cause student indiscipline at SMK Negeri 1 Sigli. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research subjects included the principal, vice principal for student affairs, and guidance and counseling teachers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the principal's strategic policies are formulated through a participatory process involving various school stakeholders and are implemented flexibly according to the conditions of the students. The principal's strategic policies have a positive effect on student disciplinary behavior and contribute to a more orderly and conducive school climate. Factors that influence student indiscipline include family environment, peer influence, economic conditions, and personal habits of students. This study concludes that the leadership of the principal and collaboration among stakeholders are important in managing student discipline in a sustainable manner